2012
DOI: 10.33225/pec/12.49.73
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Well-Being and Its Relation to Academic Performance of Students in Georgian Context

Abstract: Well-being is a dynamic concept that includes subjective, social, and psychological dimensions as well as health-related behaviors. It is often thought of as one of the hallmarks of the liberal arts experience, resulting from educational encounters that both guide students in the search for meaning and direction in life and help them realize their true potential. Research of students’ well-being is conducted in various countries, but it is the first study conducted in Georgia. The objectives of the studies we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 16 publications
1
9
0
1
Order By: Relevance
“…Based on region, the items containing a DIF were found in the psychological wellbeing factor (33 and 34), which positively influenced academic performance. This showed that higher psychological well-being led to greater academic performance (Turashvili & Japaridze, 2012). These results indicated the students with this factor possess a purpose in life and observe environmental difficulties as unproblematic challenges.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Based on region, the items containing a DIF were found in the psychological wellbeing factor (33 and 34), which positively influenced academic performance. This showed that higher psychological well-being led to greater academic performance (Turashvili & Japaridze, 2012). These results indicated the students with this factor possess a purpose in life and observe environmental difficulties as unproblematic challenges.…”
Section: Discussionmentioning
confidence: 70%
“…This shows that academic achievement is influenced by both internal and external factors. In this case, the internal factors affecting academic performance include self-efficacy (Akram & Ghazanfar, 2014;Lane & Lane, 2001), self-esteem (Iniama, 2004;Arshad et al, 2015), psychological well-being (Turashvili & Japaridze, 2012;Esteve, 2008), andprocrastination (Lakshminarayan et al, 2012). Meanwhile, the influential external factors include family and friends (Crosnoe et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oreopoulos, 2007). Neste sentido, o estudo do BES e da QV no ensino superior é essencial para conhecermos a forma como os alunos estabelecem, ou não, metas e objetivos na sua vida, criam redes sociais e se tornam ativos e autónomos, facto que pode conduzir à diminuição do abandono escolar (Turashvili & Japaridze, 2012).…”
Section: O Contributo Da Educação Aliada Ao Suporte Social No Aumento...unclassified
“…Since students are the future of any country, their psychological well-being is crucial for their personal as well as the growth the country. Students' academic life, personal growth, and career are interrelated and these could be largely affected by the psychological dysfunction (Turashvili & Japaridze, 2012). Even, Pakes & Winstone (2007) and McGuire (2004) have pointed out that severe psychological disorders and psychologically damaged childhood are two of the reasons to increase crime in society.…”
Section: Introductionmentioning
confidence: 99%